RELATIONSHIP OF RISK AND RETURN IN FORMING A FINANCIAL INVESTMENT PORTFOLIO - Haydarov Humoyun (Scholar Express Journals, 2024)
This article discusses the effective organization of investment activities in the economy, accelerating the expansion of our economic capabilities, and employing our internal capabilities and reserves.
Keywords: capabilities; employing; accelerating